(untitled) (Journal of Ideas in Health, 2025)
Background: Leptospirosis is a bacterial zoonotic disease affecting mammals including wildlife, livestock, and humans, with higher prevalence recorded in pastoral communities where close contact between animals and humans increases the risk of transmission. This study aimed to determine the seroprevalence of Leptospira serovars among livestock and livestock keepers in four selected villages of the Ngorongoro Conservation Area (NCA), during the wet season. Methods: A cross-sectional study was conducted from February to April 2022 in four villages within NCA. The convenience sampling technique was recruited to collect blood samples from 141 livestock (96 cattle, 25 sheep, and 20 goats) and 154 livestock keepers. Sera were analyzed using the Microscopic Agglutination Test (MAT) to diagnose individuals infected by Leptospira serovars. Data were analyzed using SPSS v26 with descriptive and inferential statistics including Chi-square, Kruskal-Wallis, and logistic regression. Results: The overall seroprevalence was 10.64% in livestock and 5.19% in livestock keepers. Cattle had the highest positivity (11.46%) among animals. Hebdomadis was the most frequently detected serovar in livestock, while Grippotyphosa predominated in humans. Oloirobi village recorded the highest human seroprevalence (3.25%) with a statistically significant difference compared to Endulen (p=0.007). Analysis of logistic regression showed no significant associations between seropositivity and sex or age of livestock keepers. Conclusion: The presence of Leptospira antibodies in both livestock and humans indicates ongoing exposure in the NCA. These findings underscore the need for targeted interventions including livestock vaccination programs, improved animal husbandry practices, and increased public health education for livestock keepers to reduce transmission risks and protect both animal and human health.